(untitled) (American Journal of Arts and Human Science, 2024)
Gender diversity in aviation education has long been a significant issue for the aviation industry. This review investigates gender diversity by analyzing historical participation, key barriers, and initiatives to promote inclusivity. Using a systematic approach, academic databases such as Google Scholar, JSTOR, ResearchGate, Scholarly Commons, Academia.edu, and specialized aviation industry sources were searched. Peer-reviewed articles published within the last 10 years were selected based on inclusion criteria, including relevance to aviation education and gender diversity. A thematic analysis was performed to identify significant gaps, key challenges, initiatives and outcomes to assess the current state of gender diversity in the field. This review highlights the need for comprehensive efforts to create a more inclusive educational environment to close the gender gap in aviation education and improve the industry’s overall sustainability.